Translating the Commune: Cultural Politics and the Historical Specificity of the Anarchist Text - Bruce, Donald (TTR)

(untitled) (Association canadienne de traductologie, 1994)
AbstractTranslating the Commune: Cultural Politics and the Historical Specificity of the Anarachist Text — This essay deals with three interrelated matters: the first is the role of discourse analysis and the conscious theorization of discourse typologies in translation methodologies; the second is the absence of any complete English translation of Jules Vallès's autobiographical/historical trilogy, Jacques Vingtras, comprised of L'Enfant (1879), Le Bachelier (1881), and L'insurgé (1885); and the third is the analysis of specific discursive characteristics which establish the formal and functional identity of the Discourse of the Commune. Though widely published in popular and scholarly editions in France, Vallès's novels have not been included in the lycée corpus through an act of conscious cultural exclusion. This has contributed to the exclusion of Vallès abroad and to the absence of translations of the trilogy. In order to remedy this situation the translator must be aware of the specific socio-political context surrounding these novels as well as the particular formal characteristics which make up the discourse from which these texts emerge. Radical decentralisation, narrative fragmentation, multiple enunciative positions, neologisms, a structure based on an unresolved binary dialectic, interdiscursive mixing and semantic ambiguity are common characteristics of the discourse of the Commune as they are transposed metaphorically from the anarchistic theoretical discourse of P.-J. Proudhon to the Vallès texts: these specific factors coupled with a cultural politics of exclusion have long marginalized the trilogy in various curricula and, in addition, led to its exclusion from non-francophone cultures both in the original French and in translation.